2015
DOI: 10.2105/ajph.2014.302274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systems Change and Use of Electronic Health Records on Quit Rates Among Tobacco Users in a Public Hospital System

Abstract: EHRs can be used to demonstrate that routine clinical interventions with low-income primary care patients result in reductions in tobacco use and sustained quits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“… Technology complex - External validity limited: Study conducted in the correctional setting. - Financial assistance Financial Assistance - Interoperability Interoperability Chambers, et al [ 24 ] - Improvement to quality Quality - None identified None identified - Selection bias - Surveillance Surveillance - Gender bias - Access to primary care information provides tailored quality improvement initiatives Productivity/ Efficiency - External validity limited because the gender/race demographics of the sample are not representative of the U.S. Moody-Thomas, et al [ 25 ] - Improved primary care Quality - No independent method for determining the quality of data No standards - Quasi-experimental - Intervention effective in lowering the prevalence of tobacco Health Outcomes - Patient-reported behavior on bad behavior can be tempered to avoid uncomfortable discussions. - Disease prevention Preventative Care - No similar group exists for comparison of results.…”
Section: Resultsmentioning
confidence: 99%
“… Technology complex - External validity limited: Study conducted in the correctional setting. - Financial assistance Financial Assistance - Interoperability Interoperability Chambers, et al [ 24 ] - Improvement to quality Quality - None identified None identified - Selection bias - Surveillance Surveillance - Gender bias - Access to primary care information provides tailored quality improvement initiatives Productivity/ Efficiency - External validity limited because the gender/race demographics of the sample are not representative of the U.S. Moody-Thomas, et al [ 25 ] - Improved primary care Quality - No independent method for determining the quality of data No standards - Quasi-experimental - Intervention effective in lowering the prevalence of tobacco Health Outcomes - Patient-reported behavior on bad behavior can be tempered to avoid uncomfortable discussions. - Disease prevention Preventative Care - No similar group exists for comparison of results.…”
Section: Resultsmentioning
confidence: 99%
“… Horbar et al [ 30 ] Newborns received first dose of surfactant sooner compared to previous period (21 vs. 78 min post birth, p < 0.001). Kegler et al [ 25 ] More collaborative working practices Khan et al [ 31 ] Reduction in average brain function impediment score, drop from 19.21 to 14.75 MacKenzie et al [ 32 ] Turnaround time for beds reduced 210 to 54 min in 2004, maintained (2007) Moody-Thomas et al [ 33 , 34 ] Smoking quit rates increased from 5.0 % in 2008 to 9.6 % in 2009. Parchman et al [ 48 , 49 ], Noël et al [ 47 ] Significant and sustained improvement in ACIC scores for chronic care: from 5.58 to 6.33 to 6.60 (group 1) or 5.27 to 5.99 (group 2), both p < 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…Fears of the unknown and difficulty in maintaining a chain of accountability were mentioned [ 11 , 41 ]. Without specific targets, some participants feared unstated institutional motives [ 42 ] or felt pointlessly imposed upon [ 34 ]. Other barriers to successful implementation were individuals’ resistance to change [ 24 , 33 , 34 , 41 , 44 , 47 ], reluctance by senior staff to yield to collaborative decision-making [ 24 , 27 , 47 ] and lack of financial incentives [ 47 ] or external facilitation [ 11 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Advances in electronic health record implementation and other health information technology systems enable greater consistency in documentation of measures of health, including tobacco use status. 21 Research suggests that computer-based alerts improve provider likelihood of adhering to practice guidelines. 22 , 23 While the consult service continues to grow, both in numbers of providers ordering consults and number of patients for whom orders are submitted, there are ways that the electronic medical record system could be used to help capture even more of the patients who use tobacco.…”
Section: Discussionmentioning
confidence: 99%